Role of washer size in mitigating adverse effects of bolt-hole clearance in a single-lap, single-bolt basalt composite joint - Sajid, Z. (Elsevier Ltd, 2021)
Composite bolted joints are commonly used in various load-bearing structures. However, inevitable bolt-hole clearances in bolted joints reduce joint performance. Therefore, an experimental study on the influence of washer size in alleviating the adverse effects of bolt-hole clearance in single-lap single-bolt composite joint was conducted. Nine different combinations of washer sizes and bolt-hole clearances were examined. This paper presents experimental bearing analysis, SEM micrographs and failure mechanism. The bearing analysis indicated that the detrimental effects of bolt-hole clearances, i.e., reduction in strength, stiffness, and failure strain, could be mitigated by the use of larger washer sizes in bolted joints. In order to better understand the effect of washer size on internal damages and failure mechanism, SEM imaging at various stages of the loading process was conducted. A closer inspection on the failure mechanisms of various configurations revealed that small washer damages were localised. In contrast, large washer configurations exhibited excessive fibre failure, which allows the joint to absorb more energy before the final failure. These results can be used to develop a mechanism-based model of single-lap single-bolt joints under varying washer sizes. Â© 2021 Elsevier Ltd